2023
DOI: 10.1039/d3nr05318k
|View full text |Cite
|
Sign up to set email alerts
|

Poly(lactic acid) stereocomplex microspheres as thermally tolerant optical resonators

Suharman,
Wey Yih Heah,
Hiroshi Yamagishi
et al.

Abstract: Thermally tolerant polymer optical resonators are fabricated from a stereocomplex of poly(l-lactic acid) and poly(d-lactic acid) through the oil-in-water miniemulsion method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Recently, Suharman et al reported thermally tolerant microsphere resonators from quasi-natural poly(lactic acid). 63 Upon mixing poly( l -lactic acid) and poly( d -lactic acid), polymers form a stereocomplex, which enhances thermal stability. As a result, optical resonator properties are preserved even at 230 °C, which is 70 °C higher than the acceptable temperature for homochiral microspheres of poly( l -lactic acid) or poly( d -lactic acid).…”
Section: Self-assembled Microstructures From Natural Proteins For Opt...mentioning
confidence: 99%
“…Recently, Suharman et al reported thermally tolerant microsphere resonators from quasi-natural poly(lactic acid). 63 Upon mixing poly( l -lactic acid) and poly( d -lactic acid), polymers form a stereocomplex, which enhances thermal stability. As a result, optical resonator properties are preserved even at 230 °C, which is 70 °C higher than the acceptable temperature for homochiral microspheres of poly( l -lactic acid) or poly( d -lactic acid).…”
Section: Self-assembled Microstructures From Natural Proteins For Opt...mentioning
confidence: 99%